Toxicological findings about an anticancer fraction with casearins described by traditional and alternative techniques as support to the Brazilian Unified Health System (SUS) - Pinheiro Fetreira, Paulo Michel; Santos, Denise Barbosa; Silva, Jurandy do Nascimento; Goudinho, Amanda Freitas; Silva Ramos, Carla Lorena; Souza, Patricia Canteri de; Couto de Almeida, Ricardo Sergio; Moura, Diego Sousa; Oliveira, Rhaul de; Grisolia, Cesar Koppe; Cavalheiroe, Alberto Jose [UNESP]; Carvalho Melo-Cavalcante, Ana Amelia de; et al. (Elsevier B.V., 2019)
Ethnopharmacological relevance: Extracts, essential oils and molecules from Casearia sylvestris have popularly shown pharmacological actions against chronic diseases, as anxiety, inflammation, cancer and dyslipidemia. In the context of antitumoral therapy, we investigated in vitro, ex vivo and in vivo toxicological changes induced by a Fraction with Casearins (FC) and its component Casearin X isolated from C. sylvestris on animal and vegetal cells, and upon invertebrates and mammals. Material and methods: Cytotoxicity was carried out using normal lines and absorbance and flow cytometry techniques, Artemia sauna nauplii, Danio rerio embryos and meristematic cells from Allium cepa roots. Acute and 30 days-mice analysis were done by behavioral, hematological and histological investigations and DNA/chromosomal damages detected by alkaline Cometa and micronucleus assays. Results: FC was cytotoxic against lung and fibroblasts cells and caused DNA breaks, loss of integrity and mitochondrial depolarization on ex vivo human leukocytes. It revealed 24 h-LC50 values of 48.8 and 36.7 mu g/mL on A. salina nauplii and D. rerio embryos, reduced mitotic index of A. cepa roots, leading to cell cycle arrest at metaphase and anaphase and micronuclei. FC showed i.p. and oral LD50 values of 80.9 and 267.1 mg/kg body weight. Subacute i.p. injections induced loss of weight, swelling of hepatocytes and tubules, tubular and glomerular hemorrhage, microvesicular steatosis, lung inflammatory infiltration, augment of GPT, decrease of albumin, alkaline phosphatase, glucose, erythrocytes, and lymphocytes, and neutrophilia (p > 0.05). FC-treated animals at 10 mg/kg/day i.p. caused micronuclei in bone marrow and DNA strand breaks in peripheral leukocytes. Conclusions: This research postulated suggestive side effects after use of FC-related drugs, demonstrating FC as antiproliferative and genotoxic on mammal and meristematic cells, including human leukocytes, teratogenicity upon zebrafish embryos, myelosuppression, clastogenicity, and morphological and biochemical markers indicating liver as main target for FC-induced systemic toxicity.
Keywords: Clerodane diterpenes; Embryotoxicity; Genotoxicity; Histological changes; Biochemical profile; Risk assessment